1992
DOI: 10.1021/tx00028a006
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver metabolism of benzo[b]naphtho[2,1-d]thiophene

Abstract: Thioarenes, sulfur-containing polycyclic aromatic hydrocarbons, have been detected in a number of environmental sources. The metabolism of one thioarene, benzo[b]naphtho[2,1,d]thiophene ([2,1]BNT), by F344 rat liver 9000g supernatant (S-9) was studied. [2,1]BNT which is structurally analogous and has similar carcinogenic potency to chrysene, was metabolized to six ethyl acetate-extractable metabolites when incubated with S-9 from Aroclor 1254-treated F344 rats. Each metabolite was collected from reverse-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The metabolism of thioarenes (sulphur-containing PAHs) such as dibenzothiophene, benzo(b)naphtho(2,1-d)thiophene or benzo(b)phenanthro(2,3-d)thiophene has been investigated after oral administration to rats (Ambaye et al, 1961) or using rodent liver subcellular fractions (Murphy et al, 1992;Yuan et al, 2003). The in vivo experiment conducted by Ambaye and co-workers on dibenzothiophene showed that this compound is eliminated through urine as 1-hydroxydibenzothiophene-5,5-dioxide, indicating that oxidation occurred on the sulphur atom and on the benzene ring.…”
Section: Sulphur Compoundsmentioning
confidence: 99%
“…The metabolism of thioarenes (sulphur-containing PAHs) such as dibenzothiophene, benzo(b)naphtho(2,1-d)thiophene or benzo(b)phenanthro(2,3-d)thiophene has been investigated after oral administration to rats (Ambaye et al, 1961) or using rodent liver subcellular fractions (Murphy et al, 1992;Yuan et al, 2003). The in vivo experiment conducted by Ambaye and co-workers on dibenzothiophene showed that this compound is eliminated through urine as 1-hydroxydibenzothiophene-5,5-dioxide, indicating that oxidation occurred on the sulphur atom and on the benzene ring.…”
Section: Sulphur Compoundsmentioning
confidence: 99%
“…Thiophene is a sulfur‐containing heterocyclic hydrocarbon that has been detected in a number of environmental sources as various derivatives 1,2 . Christomanos and Scholz first described neurotoxicity in dogs that had been given thiophene subcutaneously 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites of benzo[ b ]naphtho[2,1- d ]thiophene ([2,1]BNT) and benzo[ b ]phenanthro[2,3- d ]thiophene include dihydrodiols with a bay-region double bond, as well as the sulfoxide and the sulfone [8,9]. In addition, [2,1]BNT-3,4-diol, which forms a bay-region diol epoxide, was as mutagenic in Salmonella TA100 as the parent compound [2,1]BNT; however, [2,1]BNT-1,2-diol was not mutagenic [10].…”
Section: Introductionmentioning
confidence: 99%